2014
DOI: 10.1159/000363041
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Microglia by Histamine and Substance P

Abstract: Background: Activated microglia perform many of the immune effector functions typically associated with macrophages. However, the regulators involved in microglial activation are not well defined. Because microglia play a pivotal role in immune surveillance of the CNS, we studied the effect of the neuromediators histamine and substance P on microglia. Methods: The induction of microglial activation by histamine and substance P was examined using primary cultured microglia. Fluorescent images were acquired with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 55 publications
3
52
0
Order By: Relevance
“…In addition, the same laboratory reported similar results in a second paper, comparing the effects of histamine and substance P on mitochondrial membrane depolarization as well as on the production of TNF-a-, IL-6-and reactive oxygen species (ROS) of primary rat microglial cells (Zhu et al, 2014). The data suggest that histamine causes H 1 R-and H 4 R-dependent stimulation of TNF-a, IL-6 and ROS release.…”
Section: Non-neuronal Cells Of the Brainmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, the same laboratory reported similar results in a second paper, comparing the effects of histamine and substance P on mitochondrial membrane depolarization as well as on the production of TNF-a-, IL-6-and reactive oxygen species (ROS) of primary rat microglial cells (Zhu et al, 2014). The data suggest that histamine causes H 1 R-and H 4 R-dependent stimulation of TNF-a, IL-6 and ROS release.…”
Section: Non-neuronal Cells Of the Brainmentioning
confidence: 53%
“…The data suggest that histamine causes H 1 R-and H 4 R-dependent stimulation of TNF-a, IL-6 and ROS release. Interestingly, while histamine caused mitochondrial depolarization, substance P was ineffective with regard to this parameter (Zhu et al, 2014).…”
Section: Non-neuronal Cells Of the Brainmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding also raises the question of whether we are missing important therapeutic avenues by studying microglia and MCs in isolation [19]. Our previous study showed that the neuromediators histamine and SP triggered microglial activation, indicating the possibility of communication between MCs and microglia [25]. However, direct evidence concerning whether MCs could affect microglial activation was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine induces release of pro-inflammatory factors such as tumor necrosis factor-α and interleukin-6 (IL-6) from activated microglia, via H1R and H4 receptor-MAPK and PI3K/AKT-NF-kappa B signaling pathway [14]. Moreover, it induces the production of reactive oxygen species (ROS) [15]. Histamine also acts as a nitric-oxideregulating factor by stimulating inducible nitric oxide synthase expression in microglia from neonatal rat brain [16].…”
Section: Introductionmentioning
confidence: 99%